2019
DOI: 10.29252/jgbfnm.16.2.52
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Topical Application of Lavender Essential Oil on Pain Severity during Intravenous Catheterization: A Randomized Clinical Trial

Abstract: Background: Intravenous catheterization is one of the most common invasive interventions in the nursing profession which is associated with pain and patient dissatisfaction. The aim of the present study was to investigate the effect of topical lavender essential oil on the severity of pain caused by intravenous catheterization. Methods: This randomized clinical trial performed on 66 elective surgery candidates in Shahid Beheshti Hospital of Sabzevar in 2017. The eligible patients was recruited through convenie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Another active ingredient, linalyl acetate, has a narcotic function [ 25 ]. There are various studies in the literature examining the effect of aromatherapy on pain caused by the insertion of an intravenous catheter, injection insertion into the forearm, or arteriovenous (AV) fistula application via injection [ 16 , 21 , 22 , 26 – 29 ]. However, no national or international studies to our knowledge have investigated the use of topical aromatherapy during insulin injection in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another active ingredient, linalyl acetate, has a narcotic function [ 25 ]. There are various studies in the literature examining the effect of aromatherapy on pain caused by the insertion of an intravenous catheter, injection insertion into the forearm, or arteriovenous (AV) fistula application via injection [ 16 , 21 , 22 , 26 – 29 ]. However, no national or international studies to our knowledge have investigated the use of topical aromatherapy during insulin injection in diabetic patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is emphasized in the relevant literature that both inhaler [ 22 , 26 , 33 ] and topical lavender oil aromatherapy [ 34 ] significantly reduce pain during AV fistula puncture. In some other studies, lavender aromatherapy was found to significantly reduce the total pain score at the 5th and 10th min of intravenous catheter insertion in both children [ 28 ] and adults [ 29 ]. In a study examining the effect of lavender aromatherapy on the pain felt during the injection, it was reported that inhaled lavender aromatherapy applied significantly reduced pain [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several animal studies have reported the analgesic and anti-inflammatory activities of Lavandula angustifolia essential oil (LAEO) and demonstrated its important therapeutic potential for chronic pain. 15,16 Similarly, the analgesic effects of LAEO have been revealed on post-episiotomy pain in periparous women. 17 The main constituents of this plant EO include camphor, 1,8-cineole, and endo-borneol, which represent percutaneous-enhancing effects.…”
Section: Introductionmentioning
confidence: 98%
“…The flowers and EOs of LA known as ‘Ostokhoddous’, are utilized in traditional drugs to treat several disorders and conditions. Several animal studies have reported the analgesic and anti‐inflammatory activities of Lavandula angustifolia essential oil (LAEO) and demonstrated its important therapeutic potential for chronic pain 15,16 . Similarly, the analgesic effects of LAEO have been revealed on post‐episiotomy pain in periparous women 17 .…”
Section: Introductionmentioning
confidence: 99%